2012
DOI: 10.1002/eji.201142176
|View full text |Cite
|
Sign up to set email alerts
|

Generation of diversity by somatic mutation in theCamelus dromedariusT‐cell receptor gamma variable domains

Abstract: In jawed vertebrates the V-(D)-J rearrangement is the main mechanism generating limitless variations of antigen-specific receptors, immunoglobulins (IGs), and T-cell receptors (TCRs) from few genes. Once the initial diversity is established in primary lymphoid organs, further diversification occurs in IGs by somatic hypermutation, a mechanism from which rearranged TCR genes were thought to be excluded. Here, we report the locus organization and expression of the T-cell receptor gamma (TCRG) genes in the Arabia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 62 publications
3
33
0
Order By: Relevance
“…On the contrary, they found a C→T transition responsible for an Alanine to Valine amino acidic substitution when a 422 bp region of the first exon of the MYF5 gene was screened in the same animals. Vaccarelli et al (2012) detected, at the T-cell receptor (TCR) gamma genes, SNPs with a frequency of one every 114 to 485 nucleotides, depending on the considered rearrangements, and somatic hypermutation was suggested on that locus as a mechanism to diversify the Camelus dromedarius TCR gene repertoire face to the wide spectrum of antigenic determinants presented by a variety of diverse and evolving pathogens. High nucleotide sequence diversity as a consequence of somatic hypermutation had been previously reported also for the T-cell receptor delta chains (Antonacci et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, they found a C→T transition responsible for an Alanine to Valine amino acidic substitution when a 422 bp region of the first exon of the MYF5 gene was screened in the same animals. Vaccarelli et al (2012) detected, at the T-cell receptor (TCR) gamma genes, SNPs with a frequency of one every 114 to 485 nucleotides, depending on the considered rearrangements, and somatic hypermutation was suggested on that locus as a mechanism to diversify the Camelus dromedarius TCR gene repertoire face to the wide spectrum of antigenic determinants presented by a variety of diverse and evolving pathogens. High nucleotide sequence diversity as a consequence of somatic hypermutation had been previously reported also for the T-cell receptor delta chains (Antonacci et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). According to our results, the dolphin locus is the simplest of the mammalian TRG loci identified to date (Additional file 1 ) [ 9 , 10 , 21 23 ]. It spans only 48 kb and its genes are arranged in a pattern comprising 2 TRGV, 3 TRGJ genes and a single TRGC (Additional file 2 ) gene.…”
Section: Resultsmentioning
confidence: 79%
“…It was reported that somatic hypermutation contributed to the generation of diversity within the dromedary TRG and TRD variable domains (Antonacci et al, 2011;Vaccarelli et al, 2012). This represented another evolutionary innovation of the camelid immune system, as somatic hypermutation was primarily adopted in B cells to enhance antibody diversity but was rarely documented in T cells (Ciccarese et al, 2014).…”
Section: Tcr Gene Locimentioning
confidence: 99%
“…With regard to the T-cell receptors (TCRs), it was found that although the germline repertoire of dromedaries appeared limited compared to that of other artiodactyls, extensive somatic hypermutation occurred on rearranged TRDV and TRGV genes to enhance their diversity (Antonacci et al, 2011;Ciccarese et al, 2014;Vaccarelli et al, 2012). This was quite unusual, as somatic hypermutation was only documented for IGs and not for TCRs in other mammals.…”
Section: Introductionmentioning
confidence: 99%